Underwater photogrammetry reveals new links between coral reefscape traits and fishes that ensure key functions. Issue 2 (6th February 2022) - Urbina‐Barreto, Isabel; Elise, Simon; Guilhaumon, François; Bruggemann, J. Henrich; Pinel, Romain; Kulbicki, Michel; Vigliola, Laurent; Mou‐Tham, Gerard; Mahamadaly, Vincent; Facon, Mathilde; Bureau, Sophie; Peignon, Christophe; et al.
Abstract: Maintaining key functions of coral reefs is vital for the persistence of these ecosystems as well as for securing the goods and services that they provide in the Anthropocene. Underwater photogrammetry by Structure from Motion (SfM) allows the quantification of novel habitat descriptors that may be particularly relevant in assessing key reefscape traits, that is, physical and ecological characteristics of coral reef habitats. Here, we combined this new technology with fish surveys to explore how reefscape traits shape the functional structure of reef fish assemblages around three environmentally contrasted islands of the Indo‐Pacific (Europa Island, Reunion Island, and New Caledonia). At 24 sites, habitat descriptors were computed from digital elevation models (DEM) and orthomosaics, while reef fish assemblages were assessed by visual census and video footage. Four habitat descriptors were marginally correlated and presented low variance inflation factor (VIF) values, thus being the most complementary descriptors: surface complexity, total shelter capacity, Shannon Shelter Index, and total coral cover. Linear mixed models (LMM) were used to explore the relationships between these habitat descriptors and four key fish functional entities: prey, planktivores, grazers, and predators. For each model, the variance explained (i.e., marginal R 2 ) was significantly higher when considering multiple predictors, including the novel three‐dimensional descriptors (i.e., total shelter capacity and Shannon Shelter Index). The habitat descriptors quantified from underwater photogrammetry outputs (i.e., DEM and orthomosaics) provide easily available data to assess key reefscape traits and predict fish assemblage structure in coral reef ecosystems. This trait‐based functional approach allows consistent assessment of the links between these descriptors from local to regional scales. Considering the global coral reef crisis and the increasing availability of world‐reef photogrammetric surveys, this new technology should be key to bringing solutions to 21st‐century conservation issues.